The Customer and the Teller: A Close Encounter of an Unusual Kind. (February 2017) - Gopinath, Mohan; Abraham, Dolphy
Calcutta in midsummer is not an ideal place to be in. Anybody who has lived there even for a year will be the first to acknowledge this. The humidity is high, the weather is very hot, the power cuts are frequent and as a direct result of all these, tempers tend to run high. It is about a High Net Worth customer who banked with the Shakespeare Sarani (Road) branch in Calcutta of the Taiwan International Bank, who had come in at 1.45 pm to withdraw cash from his savings account. It was hot, humid, there was a power cut and the banking hall was also crowded. What then occurred gives the reader insights into various aspects of customer management and handling of unionized staff members. The discussion point of the case is management of unions. ( Note —a list of the characters who appear in the case is given at the end)